2022
DOI: 10.1055/s-0042-1750315
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome in Children (MIS-C) with COVID-19: A Single-Center Experience

Abstract: Objective Multisystem inflammatory syndrome in children (MIS-C) is a hyperinflammatory syndrome associated with multiorgan damage that occurs following coronavirus disease 2019 (COVID-19). Research on clinical and laboratory findings, and imaging studies, aiming to predict the progression to severe disease state is limited. This study recruited patients with MIS-C who presented with mild or severe symptoms from a single center in Turkey and evaluated factors related to their symptoms. Methods This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…In terms of laboratory findings, lymphopenia, thrombocytopenia, and hyponatremia are mostly expected in MIS-C and they are more prominent compared with the KD. 3,18,19,22 In our study, consistent with the literature, the mean serum sodium level was considerably lower in the MIS-C group than in the KD group. Although there was no statistically significant difference between the groups for lymphopenia, it was more frequent in the MIS-C group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In terms of laboratory findings, lymphopenia, thrombocytopenia, and hyponatremia are mostly expected in MIS-C and they are more prominent compared with the KD. 3,18,19,22 In our study, consistent with the literature, the mean serum sodium level was considerably lower in the MIS-C group than in the KD group. Although there was no statistically significant difference between the groups for lymphopenia, it was more frequent in the MIS-C group.…”
Section: Discussionsupporting
confidence: 92%
“…17 In our study, the sedimentation rate was higher in the KD group than in the MIS-C group, which was consistent with the literature. It has been reported that the levels of fibrinogen, procalcitonin, D-dimer, and ferritin were increased in MIS-C. 5,22 We obtained similar results in our MIS-C group. These differences in the clinical and laboratory findings suggest that MIS-C and KD are two different diseases with overlapping clinical features and both diseases have different immunologic phenotypes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7 Clinically, persistent fever, increased proinflammatory cytokines, and exaggerated response in inflammatory markers (CRP, ESH, D-dimer, ferritin) have been detected, resulting in multiorgan dysfunction. 1 8 In the present study, we compared the characteristics of patients with MIS-C according to disease severity and observed that the most common clinical severity of MIS-C was moderate (47%). The most common clinical symptom was fever, and the other common clinical findings were nonpurulent conjunctivitis, rashes, fatigue, and strawberry tongue.…”
Section: Discussionmentioning
confidence: 81%
“…Even though COVID-19 is usually mild in children, the clinical severity of MIS-C varies according to the organ system that is involved. 1 According to CDC data, the total number of MIS-C cases seen in the United States until August 29, 2022 was reported as 8,862 and the number of MIS-C-related deaths as 72. 2 Patients with MIS-C have various symptoms ranging from fever to cardiogenic shock.…”
Section: Introductionmentioning
confidence: 99%